New Development: Accounting Recognition of Public Infrastructure—Applying a Practical Control Criterion Approach - Ruz-Farias, V (Routledge, 2020)
The accounting recognition of public infrastructure can be extremely complex. This article explores and discusses the key IPSAS definitions and reviews the national accounting frameworks of some countries as regards their criteria for recognizing these assets. The author makes an important contribution to public sector accounting research by presenting a new way of recognizing public infrastructure as an asset based on the control criterion. IMPACT The recognition of public infrastructure assets (for example road networks, transport infrastructure, bridges) is difficult because there is insufficient guidance in current IPSAS. Public sector entities need assistance when applying the IPSAS general recognition criteria. This article provides practical guidance on the use of ‘control’ for determining which public entity should recognize an infrastructure asset in its balance sheet. It will be of value to preparers of accounts, auditors and accounting scholars, supporting them in the process of developing specific accounting recognition criterion. This practical control criterion approach can promote consistency in the application of IPSAS and prevent double-counting or omissions of assets from accounts. © 2020, © 2020 Informa UK Limited, trading as Taylor & Francis Group.